Italian neonatal birthweight charts derived from INeS not separated by birth order - Elena Spada; Chiara Peila; Alessandra Coscia (BMC, 2024)
Abstract Background Identifying high-risk neonates with abnormal fetal growth is crucial for health risk prediction and early intervention. Small for gestational age (SGA) and large for gestational age (LGA) classifications highlight neonates having a higher risk for postnatal diseases. Accurate diagnosis depends on precise anthropometric measurements and appropriate reference data. In 2010, specific neonatal charts for Italian singletons (INeS charts) were published, tracing separately for first- and later-born neonates due to a 3% birth weight difference. We present INeS charts for birth weight non-separated by first- and later-born babies useful when information on parity is unavailable or unreliable, or for better comparisons with other neonatal charts that are not separated by birth-order. Methods INeS charts were traced using a parametric function. Starting with the parameters estimates published in a different paper, INeS charts not separated by birth order were traced for the gestational age range of 23 to 42 weeks. In a second step the charts were parametrized as Cole and Green Lambda Mu and Sigma (LMS) model, allowing computation of standard deviation scores. Results The centiles of non-separated INeS charts follow between first- and later-born charts. Distances varied due to changing first-born proportions with gestational age, Max differences of about 100g with later born and 70g with first-born were observed at term. S and L functions have a similar shape for boys and girls. S function shows a pick at about 29 weeks, L function has positive values in all the range of gestational age with a pick at 39 weeks. Conclusions The study presents non-separated Birth Weight INeS charts, bridging the gap when parity information is unavailable. Differences with separated charts were generally small, making them reliable for neonatal health assessment. Insights from L and S parameters contribute to standardized birth weight and adjust it by sex and Gestational Age, useful for defining SGA or LGA neonates. The paper enhances neonatal care tools, showcasing INeS chart flexibility in different clinical scenarios and supporting neonatology research.